Characterization of the mistura alloy used for Venetian sesino coins: 16th century. (2nd October 2018) - Martorelli, D.; Bortolotti, M.; Lutterotti, L.; Pepponi, G.; Gialanella, S.
Abstract : The information provided by material investigations on ancient coins is interesting in many respects, as concerns the archaeological and historical research. In this study a set of Venetian sesino coins, minted over a period ranging from 1554 until 1605, have been investigated in order to shed light on some aspects of the so‐called mistura (mixture) alloy. The widespread diffusion of these relatively low‐value coins of the Venetian Republic, commonly used in commercial transactions in the second half of 16th century, also outside the territories of the Republic, makes them an important proxy to be used in the reconstruction of the political and historical events of the period. The specific issue of the actual composition of the mistura alloy is herewith addressed for the first time, using a combined approach based on X‐ray fluorescence and X‐ray diffraction nondestructively applied to the analysis of the samples. It turns out that the mistura alloy, traditionally regarded as a Cu‐Ag two phase alloy, over the latest period of circulation of the sesino coins, was actually made of copper only, still containing minor concentrations of lead, to be regarded as an impurity of the alloy and not as an intentional addition.